Biochemical composition of the deep-water crab Charybdis smithii - Balasubramanian, C P; Suseelan, C (Indian Journal of Fisheries, 2011)
Protien,carbohydrade,lipid,meat and water content of potentially commercialdeep-water crab Charybdis smithii were determined for various size groups. Theprotien content of meat varied from 59.8 to 71.1, lipid from 6.2 to 8.2 and carbohydratefrom 2.4 to 3.4% of dry weight, whereas, the water content ranged between85.5 and 89.6%.